Cross-Sectional Study on Cycling Position and Non-Specific Low Back Pain: Ergonomic and Pain Analysis - Mas Pramesti, Putu Waisyaka; Kinandana, Gede Parta; Juhanna, Indira Vidiari; Saraswati, Putu Ayu Sita (Majalah Ilmiah Fisioterapi Indonesia; Vol 12 No 3 (2024): Majalah Ilmiah Fisioterapi Indonesia, 2024)
Introduction : Cycling is a physical activity that enhances physical fitness and involves moving various body parts, such as muscles and bones. This activity can lead to musculoskeletal complaints, including Non-Specific Low Back Pain (NSLBP), often caused by improper cycling posture. This study investigates whether non-ergonomic cycling positions contribute to the onset of NSLBP in cyclists. Methods : This study utilized a cross-sectional design and purposive sampling technique to select subjects according to inclusion and exclusion criteria. The total sample comprised 44 cyclists. Data were collected through interviews to determine the duration, distance, and frequency of cycling, followed by pain examinations, palpation, and neurodynamic tests such as the Slump and Bragard tests. Cycling positions were assessed using the Rapid Entire Body Assessment (REBA). Results : Chi-square analysis showed a p-value of 0.001, indicating a significant relationship between cycling position and NSLBP complaints. Conclusion : This study concludes that there is a relationship between cycling position and Non-Specific Low Back Pain. Educating cyclists on ergonomics, as well as incorporating warm-up, cool-down, and stretching during breaks, can be steps to reduce NSLBP complaints.   Keywords : non-specific low back pain, cycling position, cyclists, ergonomics, back pain